2013
DOI: 10.1371/journal.pone.0070997
|View full text |Cite
|
Sign up to set email alerts
|

Separating Drought Effects from Roof Artifacts on Ecosystem Processes in a Grassland Drought Experiment

Abstract: 1Given the predictions of increased drought probabilities under various climate change scenarios, there have been numerous experimental field studies simulating drought using transparent roofs in different ecosystems and regions. Such roofs may, however, have unknown side effects, called artifacts, on the measured variables potentially confounding the experimental results. A roofed control allows the quantification of potential artifacts, which is lacking in most experiments.2We conducted a drought experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 47 publications
9
46
1
Order By: Relevance
“…After an initial phase with similar soil water content in each of the three treatments, soil water content was constantly lower under the rainout-shelter as compared to the ambient control and the rainout-shelter control plots. The soil water content in the experimental treatments started to differ after the first heavy rain events supporting results of previous studies (Mikkelsen et al, 2008;Vogel et al, 2013). Although the early summer 2017 was characterized by several short drought-like periods, the developed rainout-shelters still resulted in differences in soil water content, making the design also suitable for regions with drier climatic conditions.…”
Section: Roof Performancesupporting
confidence: 84%
See 2 more Smart Citations
“…After an initial phase with similar soil water content in each of the three treatments, soil water content was constantly lower under the rainout-shelter as compared to the ambient control and the rainout-shelter control plots. The soil water content in the experimental treatments started to differ after the first heavy rain events supporting results of previous studies (Mikkelsen et al, 2008;Vogel et al, 2013). Although the early summer 2017 was characterized by several short drought-like periods, the developed rainout-shelters still resulted in differences in soil water content, making the design also suitable for regions with drier climatic conditions.…”
Section: Roof Performancesupporting
confidence: 84%
“…Rainout-shelters may cause lower air temperature due to the interception of radiation (Yahdjian and Sala, 2002), on the one hand, on the other hand a greenhouse effect, enhanced by reduced air flow under shelters, may cause higher temperature (Svejcar et al, 1999;Vogel et al, 2013). Both artifacts may bias the results of rainout-shelter experiments.…”
Section: Microclimatementioning
confidence: 99%
See 1 more Smart Citation
“…Large interception troughs in New Mexico, USA, affected near‐surface air temperatures by up to 4°, and an air temperature effect was found in relation to distance from the troughs (Pangle et al, ). In some cases, effects of rain‐out shelters on air temperature were smaller than our night‐time increase of ~0.6 K (Kundel et al, ; Vogel et al, ), whereas other studies found a larger effect on temperature (Power et al, ). Overhead rain‐out shelters almost always reduce instantaneous PAR (Power et al, ).…”
Section: Discussioncontrasting
confidence: 62%
“…Each of the 24 plots contained three subplots (1 × 1.5 m) which were at least 1 m from each other and from the edge of the plot. Each subplot was given one of three treatments: (1) Drought (D), covered with a transparent roof to exclude rain, simulating drought; (2) Control (C), not covered with a roof; and (3) Roofed control (R), covered with a transparent roof with 5 cm holes, allowing rain to pass through, but controlling for possible roof effects such as increased temperature and decreased light intensity (Vogel et al., ). Control and roofed subplots received ambient rainfall during the 6‐week period.…”
Section: Methodsmentioning
confidence: 99%